2020
DOI: 10.1177/1538574419896735
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Long Superficial Femoral Artery–Chronic Total Occlusions Using the Gogo Catheter With IVUS Via a Popliteal Puncture Method Is Effective, Safe, and Useful

Abstract: Objectives: We aimed to investigate the usefulness of inserting a 6Fr sheath guided by duplex ultrasonography via a popliteal artery puncture. We also aimed to demonstrate endoluminal tracking using a retrograde approach using the Gogo catheter with intravascular ultrasound (IVUS). Background: The bidirectional approach is useful for increasing the success rate of the procedure for long superficial femoral artery–chronic total occlusions (SFA-CTOs). However, this procedure becomes somewhat complicated. Since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Nakamura et al 22 and Tsubakimoto et al 23 demonstrated that IVUS-guidance can help avoid subintimal or intramedial crossing routes during CTO revascularization, by retracting and redirecting the guidewire when its path threatened to damage intimal and medial tissue. Nakamura et al 59 reported feasibility and high revascularization success when using this approach during a retrograde intraluminal crossing of femoral CTOs. Moreover, Tsubakimoto et al 60 was able to achieve clinically true lumen routes in 91.1% of the IVUS-guided procedures, as opposed to 51.3% of the uoroscopy guided procedures (p<.001), leading to higher patency rates at 12 month compared to conventional uoroscopy guidance (70.0% vs 52.2%, p<.05).…”
Section: Ivus Cathetersmentioning
confidence: 99%
“…Nakamura et al 22 and Tsubakimoto et al 23 demonstrated that IVUS-guidance can help avoid subintimal or intramedial crossing routes during CTO revascularization, by retracting and redirecting the guidewire when its path threatened to damage intimal and medial tissue. Nakamura et al 59 reported feasibility and high revascularization success when using this approach during a retrograde intraluminal crossing of femoral CTOs. Moreover, Tsubakimoto et al 60 was able to achieve clinically true lumen routes in 91.1% of the IVUS-guided procedures, as opposed to 51.3% of the uoroscopy guided procedures (p<.001), leading to higher patency rates at 12 month compared to conventional uoroscopy guidance (70.0% vs 52.2%, p<.05).…”
Section: Ivus Cathetersmentioning
confidence: 99%